Preparation, modification and characterization of activated carbon derived from Macadamia nutshells and its adsorption rate and capacity for Au(CN)2- compared to commercially prepared coconut shells - Tsolele, Refiloe (Vaal University of Technology, 2017)
Activated carbons have been produced from various carbonaceous source materials including nutshells, peat, wood, coir, lignite, coal and petroleum pitch and the produced carbons have been used for adsorption of inorganic and organic compounds from numerous matrices. Activated carbons are characterized by large surface area and high degree of microporosity. The ability of activated carbon to adsorb gold from solutions, which is present in very low concentrations while loading to fairly high concentrations, has made it an attractive material for the concentration of gold from dilute solutions. Consequently, the use of activated carbons for the recovery of gold from cyanide-leached liquors has gained wide acceptance in the mining industry. However, the price of commercially prepared carbons, the time taken for them to arrive, the breakage of the carbon during transportation and the interest in utilization of various local wastes for the generation of adsorbents has led to a search of more cost effective and time friendly source for the activated carbons. The focus of this research was to conduct a study in which a comparison was conducted between untreated coconut shell derived activated carbon (CAC) and Macadamia nutshell derived activated carbon (MAC) for the adsorption of gold. These activated carbons were modified with HNO3 and H3PO4 to increase their surface adsorption properties. This was done in order to explore if these activated carbons prepared from Macadamia shells could be an attractive alternative or a complementary supplement to the coconut shell based carbons that are currently being used in the gold extraction industry. The modification of the commercially prepared Macadamia activated carbons was done with 3 different concentrations for both nitric acid and phosphoric acid. The modified activated carbons were labelled MACP20%, MACP40% and MACP60%, to signify the materials prepared from 20% (v/v) H3PO4, 40% (v/v) H3PO4 and 60% (v/v) H3PO4 , respectively . Same labelling was used for 20% (v/v) HNO3, 40% (v/v) HNO3 and 55% (v/v) HNO3 modifications to correspond to MACN20%, MACN40% and MACN55%, respectively. Also, untreated coconut shell derived activated carbon (CAC) and Macadamia nutshell derived activated carbon (MAC) were investigated for gold adsorption for comparison purposes. All the activated carbons prepared in the iii | P a g e study were characterized with Brunauer-Emmet-Teller (BET), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Thermo gravimetric analysis (TGA), elemental analysis (EL) and X-ray diffraction spectroscopy (XRD). The physical properties of the activated carbons were done by determining attrition, ash content, volatile matter, and moisture content of all the activated carbons. Various parameters that affect selective adsorption such as the effect of initial concentration, time, agitation speed, interfering species, and dose of the adsorbent were investigated. Optimal parameters for gold ion adsorption were as follows: solution pH, 10; contact time, 6 h; agitation speed 150 rpm; sorbent amount 4 g and 5.5 ppm for initial concentration of gold. The observed selectivity order was not the same for all the adsorbents but the adsorption of gold was found to be mostly influenced by the presence of nickel and least influenced by copper. The MACP60% was found to be the most effective from the three concentrations investigated for the phosphoric acid modified activated carbons yet proved to have lower adsorption capabilities compared to CAC. The MACN55% was found to be the most efficient and displayed similar adsorption capabilities to those of CAC.
M. Tech (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Activated carbon; Macadamia nutshells; Adsorption rate and capacity for Au(CN)2; Coconut shells; Gold extraction; Dissertations, Academic -- South Africa; Macadamia nut; Carbon sequestration; Coconut; Adsorption; Solution (Chemistry); Gold extraction (Mining)